Biohacks And Diabetes: Obstacle Or Opportunity - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
This communication describes the concept of biohacking, and relates it to primary diabetes care. Biohacking can be defined as the use of self-developed, informal non evidence based means of managing and monitoring disease, or promoting health. In the context of diabetes care, biohacks may be related to lifestyle, diet, physical activity or spiritual management, pharmacological therapy, or monitoring strategies. These may be an obstacle, as well as an opportunity, for better health care. Empathetic listening and education is the key to incorporating biohacks as allies in the fight against diabetes. Keywords: Biohacks, person centred care, patient education, quinary prevention, therapeutic patient education.